2007
DOI: 10.4049/jimmunol.179.10.6952
|View full text |Cite
|
Sign up to set email alerts
|

The Aryl Hydrocarbon Receptor Is Required for Optimal Resistance to Listeria monocytogenes Infection in Mice

Abstract: The aryl hydrocarbon receptor (AhR) is part of a powerful signaling system that is triggered by xenobiotic agents such as polychlorinated hydrocarbons and polycyclic aromatic hydrocarbons. Although activation of the AhR by 2,3,7,8-tetrachlorodibenzo-p-dioxin or certain polycyclic aromatic hydrocarbons can lead to immunosuppression, there is also increasing evidence that the AhR regulates certain normal developmental processes. In this study, we asked whether the AhR plays a role in host resistance using murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
57
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 55 publications
3
57
0
1
Order By: Relevance
“…Memory response against a protein Ag was reported (8). However, they are more susceptible to infections with Helicobacter hepaticus, an opportunistic infection indicating immunodeficiency (50,51), and to L.monocytogenes (52). The underlying cause may be specific defects in the immune system or other general damages resulting from AhR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Memory response against a protein Ag was reported (8). However, they are more susceptible to infections with Helicobacter hepaticus, an opportunistic infection indicating immunodeficiency (50,51), and to L.monocytogenes (52). The underlying cause may be specific defects in the immune system or other general damages resulting from AhR deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the Ahr(Ϫ/Ϫ) knockout mouse displays patent ductus venosus and other arteriovenous-shunt problems (Lahvis et al, 2005), along with immune dysregulation (FernandezSalguero et al, 1995), and increased susceptibility to infection (Shi et al, 2007)-probably caused also by perturbation of eicosanoid function. Indeed, six different prostaglandins (albeit at relatively high concentrations) have been shown to activate the AHR and induce the CYP1 enzymes (Seidel et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The major immune mechanisms controlled by AhR are related to the activation and differentiation of specific T cell subsets (T regulatory [Treg] and Th17) and antigenpresenting cells (3). In the context of immunity to infections, it was demonstrated that AhR is an essential protein for murine resistance to Listeria monocytogenes (7) and toxoplasmosis (8).…”
mentioning
confidence: 99%